Different demographic pathways of the post- Socialist transition - Graovac Matassi, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
The paper discusses the COVID-19 mortality in Slovenia and Croatia in 2020 and 2021. The aim of the paper is to determine similarities and differences in mortality trends during COVID-19 period and to discuss the underlying causes and consequences. It is hypothesised that the unfavourable age structure of both countries was a catalyst of the excess mortality differentials, and that the different paths of post-socialist transitions significantly contributed to differential mortality in 2020. The analyses confirmed a biased effect of the excess mortality indicator, which is applicable only if supported with sufficient attributive data. Moreover, findings confirmed the hypothesis that COVID-19 mortality largely contributed to overall mortality in Slovenia in 2020, particularly due to the increased mortality in long-term care facilities (LTCF) which was about 70% higher compared to that of Croatia.
Keywords: coronavirus; covid-19; Croatia; excess mortality; Hrvaška; koronavirus; post-socialism; postsocializem; presežna umrljivost; SARS-CoV-2; Slovenia; Slovenija